Model-Based Exposure–Response Analysis of Apixaban to Quantify Bleeding Risk in Special Populations of Subjects Undergoing Orthopedic Surgery - Leil, T A (Nature Publishing Group, 2014)
Population pharmacokinetic (PK) and exposure–response analyses of apixaban were performed using data from phase I–III studies to predict bleeding risks for patients receiving apixaban 2.5 mg b.i.d. after total knee or hip replacement (TKR, THR) surgery (N = 5,510). Renal function, age, gender, and body weight impacted apixaban exposure. Bleeding risk increased as a function of exposure. Predicted bleeding frequencies for TKR and THR populations at risk for high apixaban exposure (female, age > 75 years, calculated creatinine clearance (cCrCL) < 30 ml/min, body weight < 50 kg) (6.85 and 10.3%, respectively) were comparable to the reference population (male/female, age 65−75 years, cCrCL ≥ 80 ml/min, body weight 65−85 kg) (6.18 and 9.32%, respectively). A 100% increase in apixaban exposure is expected to raise bleeding frequencies to 7.25% (TKR) and 10.9% (THR), whereas a 200% increase would raise them to 8.49 and 12.7%. Coexistence of combined patient risk factors or doubling of exposure is not likely to result in a substantial, clinically relevant increase in bleeding risk with 2.5 mg b.i.d. apixaban.